Audience Viewing Pleasure and Theatre on Digital Media Site: Enhancing Theatre through Digital Media (Journal of Advances and Scholarly Researches in Allied Education, 2020)
The merging of theatre and digital media allows viewers to engage in new forms of viewingpleasures and communication. The research will be important in determining if theatre as an art form cansurvive in the age of modern communication technology. Theatre is one of the earliest art forms, havingnot only endured but also incorporated and adjusted to technological developments. This research looksinto whether new media platforms can enhance theatre by enhancing the viewer's interest in the liveperformance and allowing for real-time involvement. This paper investigates young people's theatreviewing pleasures via new digital media sites. The study employs chi-square analysis to assess youngperceptions of theatre viewing on digital media platforms.The study investigates several view points onhow integrating new media and theatre might strengthen theatre as an art form. The research will aid inthe discovery of new digital media presentation and advancement opportunities for theatre. The researchwill be useful in understanding how new digital media might enhance theatre viewing pleasure.